Endoscopic, Ultrasonographic, and Histologic Descriptions of Dextranomer/Hyaluronic Acid in a Case of Fecal Incontinence - Trent Irwin; Alexandria R. Snow; Taylor S. Orton; Christie Elliott (Case Reports in Pathology)
Objective. To present a case of fecal incontinence treated with dextranomer/hyaluronic acid (Solesta®) injections, which later caused clinical confusion and avoidable interventions. The endoscopic, ultrasonographic, and histologic appearances of dextranomer/hyaluronic acid will also be reported. Case Presentation. A middle-aged Hispanic male who failed conservative management of his fecal incontinence was injected with dextranomer/hyaluronic acid in an attempt to alleviate symptoms. An unrelated screening colonoscopy was performed soon after, revealing a submucosal rectal lesion. Flexible sigmoidoscopy and endoscopic rectal ultrasound with FNA were scheduled for patient for further evaluation. An unknown foreign material was noted under microscopy and, upon attaining additional history, the gastroenterologist uncovered the patient’s recent injections of dextranomer/hyaluronic acid. Conclusion. Dextranomer/hyaluronic acid for the treatment of fecal incontinence has become more common in recent years. Though the imaging and histologic appearance of this gel-like material is seen in other areas of medicine, equivalent descriptions are limited in the anorectal region. To curb misdiagnoses and prevent unnecessary interventions, it is important to expound on the endoscopic, imaging, and histopathologic features of this tissue-bulking agent in the setting of fecal incontinence and to encourage communication, proper documentation, and easy accessibility to patient health information by all medical staff.